'You're opening yourself up to new and different ideas': Clinical psychologists' understandings and experiences of using reflective practice in clinical work: an interpretative phenomenological analysis. Issue 4 (3rd July 2020) - Carmichael, Kirsty; Rushworth, Imogen; Fisher, Paul
ABSTRACT: Reflective practice is an essential competency in clinical psychology training and practice. However, evidence is limited to support the role of reflection in clinical practice. This study investigated the lived experiences of clinical psychologists' use of reflective practice in the context of their clinical work. Seven clinical psychologists completed reflective diaries and semi-structured interviews to facilitate in-depth reflections on clinical events. Interview transcripts were analyzed using interpretative phenomenological analysis. Three superordinate themes and six subthemes were developed from the data: Exploratory Questioning (gaining a different perspective, new insight, and opening new possibilities), Containment of own Thoughts and Feelings in Practice, and Human Survival (managing the emotional impact, self-sustaining and leaving work at work). Consideration of these findings suggested that reflective practice plays a key role in clinical psychologists' perspective-taking abilities; allowing them to maintain an open and curious clinical perspective. Reflective practice enables containment, which impacts the building and maintaining of therapeutic relationships. Reflective practice relieves discomfort and promotes personal resilience. Further research on clinician use of reflective practice can contribute to understanding this core competency which is highly relevant to the training and ongoing development of clinical psychologists.